The effectiveness of a remote controlled format of speech therapy sessions in restoring patients’ speech after operations for oral and oropharyngeal cancer - E. A. Krasavina; E. L. Choinzonov; D. E. Kulbakin; N. A. Medova; Ch. S. C. Aslonova; M. L. Isaeva; I. G. Kargalskaya (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Background. Restoration of speech function after surgery for oral and oropharyngeal cancer is a complex and lengthy process, the effectiveness of which largely depends on control over corrective speech therapy. Telemedicine has become the fastest growing sector of health care, and its use for speech rehabilitation will allow speech therapy sessions to be conducted regardless of the patient’s physical location. The objective of the study was to evaluate the effectiveness of remote controlled format of speech therapy sessions in patients who underwent surgery for oral and oropharyngeal cancers.Methods and materials. The study included 36 patients aged 26 to 68 years, diagnosed with oral and oropharyngeal cancer, with a tumor prevalence of T1-3N0-2M0. The patients lived in various regions of the Russian Federation. All patients had speech function disorders after surgery for oral and oropharyngeal cancer. Remote controlled speech rehabilitation was conducted using the «Teleoncocenter» platform according to the techniques developed at the Cancer Research Institute of the Tomsk National Research Medical Center. The effectiveness of speech rehabilitation was assessed by the changes in the indicators of pronunciation disorders of groups of consonant sounds in points (from 0 to 4 points).Results. The number of online speech therapy sessions depended on the severity of speech impairment and varied from 13 to 32 (Me=21). The duration of sessions was set by the speech therapist (15–45 minutes) depending on the tasks at the current stage of speech rehabilitation therapy and the general well-being of the patient. Remote controlled speech therapy resulted in a significant improvement of the pronunciation of the studied groups of consonant sounds (p <0.001). In the groups of back-lingual and front-lingual sounds, in some cases, it was possible to achieve complete restoration of the pronunciation of sounds (0 points).Conclusion. The use of remote controlled format of speech rehabilitation demonstrated the effectiveness of correcting speech disorders after surgery in oral and oropharyngeal cancer patients. The use of the «Teleoncocenter» platform made it possible to conduct online speech therapy sessions and consultations, which was especially important for people in remote areas of the Russian Federation or who had limited opportunities to visit specialists.